2021
DOI: 10.55563/clinexprheumatol/z6drbj
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biological agents on vascular structural lesions in Takayasu's arteritis

Abstract: Objective. The aim of the present study was to evaluate the effects of biological disease-modifying anti-rheumatic drugs (bDMARDs) administered to patients with Takayasu's arteritis (TAK) on disease activity and vascular damage. Methods. This study included TAK patients who were receiving bDMARDs for at least six months. Disease activity (National Institutes of Health [NIH]), vascular lesions, and vascular damage (Combined Arteritis Damage Score [CARDS]) scores were determined. Results. There were 21 TAK patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This implies that serum IgG level could serve as a simple and useful biomarker to assess disease activity in patients with TAK. Thus far, a recommended treatment strategy for TAK involves a combination of glucocorticoids with non-biological immunosuppressive agents (for all cases) or biological agents targeting interleukin-6 or tumour necrosis factoralpha (for refractory cases) (28,29). In this study, we monitored peripheral B cell counts, serum Ig levels, and other disease activity parameters after receiving immunotherapy for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that serum IgG level could serve as a simple and useful biomarker to assess disease activity in patients with TAK. Thus far, a recommended treatment strategy for TAK involves a combination of glucocorticoids with non-biological immunosuppressive agents (for all cases) or biological agents targeting interleukin-6 or tumour necrosis factoralpha (for refractory cases) (28,29). In this study, we monitored peripheral B cell counts, serum Ig levels, and other disease activity parameters after receiving immunotherapy for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TAK patients exert a specific Tfh cell signature in circulating and aorta-infiltrating CD4 T cells (38), while the potential role of AMPK in such T cell lineages remains inclusive. In addition, biological agents that are used in TAK treatment are capable of remedying certain vascular lesions (39), suggesting specific treatment such as steroids and methotrexate could influence the results obtained. Herein, although we observed that TAK T cells showed higher p-AMPK and untreated TAK T cells tended to exert higher p-AMPK than those under concomitant treatments (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive regimens based on corticosteroids and azathioprine have reported at least a partial clinical response in 84% of patients, achieving angiographic stabilization, although with no regression of significant stenosis 15 . Clinical studies with tocilizumab, an IL-6 receptor antibody, suggest stabilization or regression of stenosis in 71-86% of treated patients 16,17 . Retrospective cohort studies comparing coronary artery bypass graft (CABG) versus PCI have described similar cardiovascular mortality, albeit PCI have been associated with higher restenosis rates 13,14,18,19 .…”
Section: Discussionmentioning
confidence: 99%